Problems of Choquet Integral Practical Applications - Sergey Sakulin; Alexander Alfimtsev (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2013)
Choquet integral with respect to fuzzy measure is a generalization of weighted arithmetic mean aggregation operator. It allows taking into account the phenomenon of dependence between criteria. Due to this it is possible to reflect the expert knowledge more accurately without making the model simplification which is the assumption of independence of the aggregation criteria. The problems of Choquet fuzzy integral applications and possible ways of overcoming them are discussed. Practical applications for this relatively new apparatus are reviewed.